2017
DOI: 10.1111/ecin.12475
|View full text |Cite
|
Sign up to set email alerts
|

Inequality and Growth in the United States: Why Physical and Human Capital Matter

Abstract: We investigate the relationship between economic growth and top income inequality under the influence of human and physical capital accumulation, using an annual panel of U.S. state‐level data. Our analysis is based upon the “unified” framework offered by Galor and Moav (2004) while the empirics account for cross‐section dependence, parameter heterogeneity, and endogeneity, in nonstationary series. We conclude that changes in inequality do not influence growth, neither in the short run nor in the long run in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 73 publications
2
11
0
Order By: Relevance
“…The theory developed by Galor and Moav () proposes a positive effect of inequality on the process of development in the early stages of industrialization when physical capital accumulation was the prime engine of economic growth but it proposes a negative effect in later stages of development when human capital accumulation becomes a prime engine of economic growth and credit constraints are largely binding. Benos and Karagiannis () provide support for the theoretical prediction of the unified theory of inequality and growth that was developed by Galor and Moav (). Banerjee and Newman () and Aghion and Bolton () suggest that equality positively affects the investment opportunities of individuals, not only in human capital but also in physical capital…”
Section: Related Literaturementioning
confidence: 66%
“…The theory developed by Galor and Moav () proposes a positive effect of inequality on the process of development in the early stages of industrialization when physical capital accumulation was the prime engine of economic growth but it proposes a negative effect in later stages of development when human capital accumulation becomes a prime engine of economic growth and credit constraints are largely binding. Benos and Karagiannis () provide support for the theoretical prediction of the unified theory of inequality and growth that was developed by Galor and Moav (). Banerjee and Newman () and Aghion and Bolton () suggest that equality positively affects the investment opportunities of individuals, not only in human capital but also in physical capital…”
Section: Related Literaturementioning
confidence: 66%
“…In that regard, inequality is negatively correlated with the level of economic development. Galor and Moav (2004) theoretical model has been empirically verified by Chambers and Krause (2010) and Benos and Karagiannis (2018). In our empirical model, we use GDP per capita as a threshold variable to differentiate between development levels.…”
Section: Inequality Globalization and Skilled Biased Technological Changementioning
confidence: 95%
“…In addition, several studies have yielded inconclusive findings, with most reporting that the relationship is positive in high-income and negative in low-income countries (see, for example, [13 , 20 , 25 , 27] ). A few studies found no relationship between inequality and growth (see [15 , 44] ).…”
Section: Overviewmentioning
confidence: 99%
“…The findings confirmed that economic growth reduced poverty, but had no effect on income inequality, which implies that there was no relationship between income inequality and economic growth. Benos and Karagiannis [15] examined the relationship between top income inequality and growth under the influence of physical and human capital accumulation in the U.S. By using 2SLS and GMM on the annual panel of U.S. state-level data during 1929 to 2013, they concluded that changes in inequality do not have an impact on growth. Table 1 shows the summary of empirical studies discussed in this section.…”
Section: Income Inequality and Economic Growth: Empirical Evidencementioning
confidence: 99%
See 1 more Smart Citation